Modelo para avaliação estratégica de redes de cooperação - Garza, Adriana Yolanda Morales (2018)
Globalization has caused an increase in market competition; because of this, in the last decades, firms have been looking for different ways to survive and generate high profits. Strategic alliances have become popular among corporations, as a way to reduce costs, gain knowledge, generate more innovative products, obtain different distribution channels, among other advantages. However, these types of organizations are not always successful. There is a lack of models in the literature that can evaluate the performance of partnerships and of each individual company making part of it. Thus, this study aims to develop a new generic model that can evaluate the performance of horizontal and vertical alliances, and also provide information about the business strategy that each different alliance should focus on to improve its performance. The new 3D model is based on two existing models, the Weise Model (2005) and the Petter Model (2012). In order to prove its applicability, it was implemented in two different strategic alliances in Santa Maria, RS, Sonnen Energia and APL - Metal Centro. Results from the evaluation of the performance of these two strategic alliances using the 3D Model, provide the users key information to ensure success in their short and long-term goals.